Relationship between agronomic and silage quality traits of forage sorghum cultivars - J. White; K. Bolsen; B. Kirch (Kansas Agricultural Experiment Station Research Reports, 1988)
Results from two trials evaluating 11 forage sorghums as silage crops indicated that silage quality traits of voluntary intake, digestibility, and crude protein content were linearly associated with the agronomic characteristics of days to half bloom and plant height. Intake was negatively associated with plant height (r = -.49); digestibility was negatively associated with days to half bloom (r = -.39) and plant height (r = -.49); and crude protein was negatively associated with days to half bloom (r = - .51) and plant height (r = -. 71). Within the same cultivar, but between years, voluntary intake varied by as much as 30 percent, digestibility by 13 percent, and protein content by 12.5 percent. Forage sorghums were also compared to grain sorghum and corn hybrids.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen' s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; Forage sorghum; Voluntary intake; Digestibility; crude protein content